Counteraction to sabotage measures on ammunition depots in the context of hybrid warfare - Ye. V. Karmannyi; M. V. Lys (Law and Safety)
The state of the military sector is one of the most important indicators of the state’s development, it also determines the level of influence of the country on the economic and political situation that is taking place on the international scene. Ensuring the proper state of Ukraine’s national security is accompanied not only by the mentioned factors, but also by the fact that our state is in a military conflict with the Russian Federation. The article is focused on studying the issues related to the nature of the modern hybrid warfare in Ukraine, an act of sabotage was considered as one of the ways of such a war, it analyzed the acts of sabotage, the object of which is ammunition depots placed on the territory of Ukraine. The suggestions for improving and refining the system of counteraction to acts of sabotage are provided.